2005
DOI: 10.1111/j.1440-1770.2005.00267.x
|View full text |Cite
|
Sign up to set email alerts
|

Geochemistry of the sediments of the El‐Kabir River and Akkar watershed in Syria and Lebanon

Abstract: A total of 39 sediment samples were collected from the El-Kabir River and its major tributaries during the low-flow period of August/September 2001. Of these samples, six were selected for a scan for pesticide residues, polychlorinated biphenyls and polycyclic aromatic hydrocarbons (PAHs). An additional seven samples were analysed for major elements and trace elements. Despite the limited number of samples analysed, it can be concluded that major elements reflect the distribution and chemistry of major rock ty… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
3
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 10 publications
2
3
0
Order By: Relevance
“…These levels are in the low range of the mean earth crust composition (Table 4) especially for carbonate rocks which, according to Kabata-Pendias and Pendias (1992), have Pb concentrations that fluctuate between 3 and 10 µg g -1 , while typical Pb concentrations are 23 µg g -1 in schist and granite, 10 µg g -1 in sandstone and very low in some magmatic rocks such as gabbro (2 µg g -1 ). However, they are comparable to the first measurements made in the Akkar watershed sediments (Thomas et al, 2005) and the marine sediment of the adjacent Batroun region (Table 4). The vertical profile of Pb concentrations exhibited its highest value (16 µg g -1 ) and quite large variations within the first 12-14 cm below the water sediment interface, and then regularly decreased from 14 to 6 µg g -1 downward in the core (Fig.…”
Section: Akkarsupporting
confidence: 86%
“…These levels are in the low range of the mean earth crust composition (Table 4) especially for carbonate rocks which, according to Kabata-Pendias and Pendias (1992), have Pb concentrations that fluctuate between 3 and 10 µg g -1 , while typical Pb concentrations are 23 µg g -1 in schist and granite, 10 µg g -1 in sandstone and very low in some magmatic rocks such as gabbro (2 µg g -1 ). However, they are comparable to the first measurements made in the Akkar watershed sediments (Thomas et al, 2005) and the marine sediment of the adjacent Batroun region (Table 4). The vertical profile of Pb concentrations exhibited its highest value (16 µg g -1 ) and quite large variations within the first 12-14 cm below the water sediment interface, and then regularly decreased from 14 to 6 µg g -1 downward in the core (Fig.…”
Section: Akkarsupporting
confidence: 86%
“…from urbanized cities (Tripoli, Jounieh, Dora, and Tyr)(Manneh et al, 2016) and Tripoli harbor(Merhaby et al, 2015) and in soil collected from different cities(Soukarieh et al, 2018). Similarly, the levels of PCBs found in the present study were more comparable to riverine sediments from the El Kebir river(Thomas et al, 2005) and lower than those found in coastal sediments from Tripoli harbor(Merhaby et al, 2015) (TableS8).The global comparison of PAHs levels shows lower concentration found in this study than rivers in China (Xu et al, 2016; Huang et al, 2017), Malaysia (Keshavarzifard et al, 2014), Taiwan (Tu et al, 2018), France (Kanzari et al, 2014; Net et al, 2015), Spain (Navarro et al, 2010), Germany (Liu et al, 2013) and Australia (Liu et al, 2017). For PCBs, lower concentrations found in this study from levels found in Haihe, Kaifaqu, Dagu, and Yongdingxin rivers, China (Liu et al, 2007), Huveaune river, France (Kanzari et al, 2014), and Niagara river, United States (Samara et al, 2006).…”
supporting
confidence: 77%
“…Despite these different potential risks associated with legacy and emerging contaminants, few studies have focused on the assessment of small Mediterranean rivers situation, especially in the eastern Mediterranean. Few studies have been conducted on the occurrence of POPs and emerging contaminants in Lebanese riverine sediments (Thomas et al, 2005; Amine et al, 2012; Amine et al, 2018a; Amine et al, 2018b). Comparatives studies between the occurrence of PAHs, UVFs, and APs within transition zones of small Mediterranean rivers in Northern Lebanon, El Kebir, El Bared, and Kadicha rivers, pointed out that the highest levels of the studied contaminants were within the Kadicha river (Amine et al, 2012;Amine et al, 2018a;Amine et al, 2018b).…”
Section: Introductionmentioning
confidence: 99%
“…The quality of the sediments in Byblos and Beirut varies from unpolluted to moderately polluted and from moderately to strongly polluted in Arida where also the V level in mussels is high (Figure 7). This pollution at Arida may be due to the El Kabir River, which carries fertilizers used in agriculture (Thomas et al, 2005). In fact, phosphate fertilizers naturally contain divanadium pentoxide due to the processing of phosphate rock (Mortvedt and Beaton, 1995).…”
Section: Discussion I Geo and Worldwide Comparisons Of Trace Metal Lementioning
confidence: 99%